Hazard Identification during Simultaneous Production and Drilling at Bayan-B Platform - Nur Liyana Shafie; Roslina Mohammad (Journal of Advanced Research in Applied Mechanics, 2021)
This paper aimed to reduce the risk at the BYDP-B platform by performing risk control. The main objectives of hazard identification are (1) to identify and assess all potential hazards, including Major Accident Hazards (MAH) with the potential to affect personnel, the environment, assets, reputation, and surrounding effects on the facilities, (2) to identify causes/ threats, potential consequences and safety measures that are in place or to be implemented to reduce the risk to persons, asset or the environment arising from those hazards, (3) to identify a safeguard proposed into the design that will aid in reducing the severity of consequences in a threat, (4) to assess risk level for high, medium or low based the frequency or likelihood of the hazardous event and the consequence of the event against personnel, environment and assets and, (5) to identify any recommendations or risk reduction measures required to help reduce the risk if it is assessed that the engineering controls are insufficient relative to the severity of the threat. Latest or modern technologies in designing a complex platform will lead to the systematic method to identify the hazard. Hazard identification (HAZID) is a technique for identifying potential hazards and threats early and can be categorized as Conceptual HAZID and Detailed HAZID. The importance of HAZID is the first activity of identifying and assess all the critical hazards. Therefore, it will provide safe and cost-effective design engineering with the lowest cost of change penalty. Generally, petroleum and natural gas demand had increased progressively in the years, business of SIPROD industry is flourishing, and hence need a safety guideline to be developed. Safety operating guidelines are not new for an HSE study in the SIPROD industry since a Deepwater Horizon accident has shocked the entire world. This is important as although all HSE hazards have been notified, the injuries and near-miss accidents also still happen at the SIPROD platform.